Pendidikan Kesehatan Pada Remaja Wanita Tentang Kesehatan Reproduksi Berkaitan Dengan Menstruasi - Rahmawati, Agustini Liviana Dwi; Putri, Gusrina Komara; Naulia, Resi Putri (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
If reproductive health knowledge is given as a teenager (an age that is identical to puberty), teenagers will grow and develop into a healthy and efficient generation. Teenagers often have difficulty finding the right information about reproductive health, giving rise to various perceptions that are not necessarily true. Knowledge about reproductive health is useful for teenagers to face the various physical, social and psychological changes they experience. Apart from that, it helps teenagers maintain reproductive health and prevent problems resulting from disorders in maintaining reproductive health. Reproductive health goals related to menstruation and the cleanliness of the reproductive organs during the menstrual phase require self-awareness of personal hygiene. To increase awareness, it must be complemented by a level of knowledge that begins in adolescence. The method used in health education activities will be face-to-face and will be held on December 6 2023. This counseling is intended so that with the time available, the material can be delivered in full. With explanations, discussions and questions and answers, participants can build knowledge and awareness of reproductive health related to menstruation and reproductive organ hygiene in the correct menstrual phase. The results after carrying out reproductive health education activities for female students at YPS Jakarta Islamic Vocational School showed that the students' knowledge increased based on the results of the pre-test and post-test that we provided.